Reflections on the specific knowledge of a teacher education program in biological sciences (Revista Contexto & Educação, 2026)
Conventionally, specific training is defined as that which is strictly composed of biological content. However, considering the nature and purpose – teacher education – the following question is fundamental: what other knowledge, besides that strictly linked to biological knowledge, can be considered specific in a teacher education program in Biological Sciences? To this end, we aimed to analyze the presence and curricular organization of teaching knowledge in teacher education program in Biological Sciences at a federal public university: the “Universidade Federal da Fronteira Sul (UFFS), Campus Cerro Largo”. We identified and analyzed the institutional curricular organization based on the existence of a specific domain and the classification of the nature of the curricular components, as well as their workload in relation to the teaching knowledge present therein. This allowed us to perceive a broadening of what is considered, in the analyzed curriculum, as specific knowledge, in addition to conceptual knowledge to be taught from Biological Sciences: pedagogical knowledge to teach the respective area of ​​knowledge, as well as knowledge derived from the situated professional context. These combined areas of knowledge form a synthesis of specific expertise that we call professional teaching knowledge in Biological Sciences.
Keywords: Teaching knowledge; Teacher education; Specific training; Professional development; Curriculum